1984
DOI: 10.1007/bf00043085
|View full text |Cite
|
Sign up to set email alerts
|

Organogenesis in callus derived from stem and leaf tissues of apple and cherry rootstocks

Abstract: Callus formation from stem internodes of the apple rootstocks M.9, M.25, M.26, M.27 and the cherry rootstock Colt, and from pith of Nicotiana tabacum cv. Wisconsin 38 was initiated on 4 c~-naphthaleneacetic acid (NAA)-based media (2.0-10.0mgl-~). Transfer of callus to corresponding media lacking NAA allowed regeneration of shoots from callus of M.25, M. 27, Colt and tobacco but not of M.9 and M.26. With M.25 phloroglucinol (PG) depressed regeneration from 30 to 10% and no regeneration was observed in cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
4

Year Published

1987
1987
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 16 publications
1
11
1
4
Order By: Relevance
“…However, there were indications that the conditions required for plantlet regeneration were much more critical for leaf discs than for internodal stem segments. The latter regenerated with zeatin/2,4-D, BAP/2,4-D (Tables 4 and 5) and B A P / I B A combinations (2.0 and 0.1 mg 1 -~, respectively, unreported data), whereas the former regenerated only with the BAP/ IBA mixture (2.0 and 0.1 m g l -t, respectively) ( Tables 3 and 6) This contrasts with the situation in apple, where leaf discs o f apple root stocks regenerated more easily than internodal segments [11]. !…”
Section: Resultscontrasting
confidence: 43%
“…However, there were indications that the conditions required for plantlet regeneration were much more critical for leaf discs than for internodal stem segments. The latter regenerated with zeatin/2,4-D, BAP/2,4-D (Tables 4 and 5) and B A P / I B A combinations (2.0 and 0.1 mg 1 -~, respectively, unreported data), whereas the former regenerated only with the BAP/ IBA mixture (2.0 and 0.1 m g l -t, respectively) ( Tables 3 and 6) This contrasts with the situation in apple, where leaf discs o f apple root stocks regenerated more easily than internodal segments [11]. !…”
Section: Resultscontrasting
confidence: 43%
“…Use of whole leaves, even with the midrib cut as done here, is simpler than collecting leaf disks from in vitro grown leaves [3,4] or cutting the leaf blades into 1 mm wide strips [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The latter purpose would be of particular interest with apples where conventional breeding programs have had relatively little impact upon commercial apple production. Regeneration of adventitious shoots has been reported from apple cotyledons [7,8,9,12,13], embryo axes [6], seedling leaves and hypocotyls [11], callus initiated from both seedling leaves [11] and roots of intact microplants of M.25 rootstock [5], and from leaves or leaf disks obtained from in vitro propagated shoots [2,3,4,16,18,19] or greenhouse-grown plants [12] of mature clones. 1 The media used for these studies contained benzyladenine (BA) plus an auxin and, in some cases [6,7,8,9], coconut milk.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern of development was determined mostly by plant species and medium constituents. James et al (1984) reported that Malus rootstocks M 25 and M 27 could be regenerated from leaf segments on the same medium, however, M 9 and M 26 could not be regenerated using the same protocol. In sweet and sour cherry, cultivar-medium dependence in adventitious shoot regeneration from in vitro leaves was well demonstrated (Tang et al 2002).…”
Section: Rooting Of Shoots and Plant Establishmentmentioning
confidence: 99%